A strategy to fast determine Chaboche elasto-plastic model parameters by considering ratcheting. (May 2019) - Liu, Shijie; Liang, Guozhu; Yang, Yichuan
Abstract: Ratcheting simulation for steel material is of importance especially when it is subjected to asymmetrical cyclic loading. A strategy to fast determine the Chaboche elasto-plastic model parameters is proposed by considering the ratcheting effect. First, one cyclic ascend experimental test with an equal strain increment of ±0.1% after each twenty-cycle loading phase up to ±1.2% is performed to observe the Masing effect. Then, a strain-controlled fatigue test is conducted at a strain range of ±0.8% to identify the parameters of Chaboche combined hardening model. Besides, a ratcheting test with stress variation from −361.6 MPa to 441.6 Mpa is executed. Based on these experiments, two computational programs are carried out to simulate the cyclic stress-strain response and ratcheting, respectively. In the parameters identification process, a pseudo-percent allocation method is developed to reduce the stress overestimation. Results indicate that: (i) 304SS presents Masing effect when the strain range is bound within ±0.9%, and it follows the previous experimental results about the serrated flow and ratcheting; (ii) The Armstrong-Frederick rules reverse in a small strain when the isotropic hardening considered, so the predicted ratcheting strains for the first few cycles are inevitably underestimated; (iii) Not only the third Armstrong-Frederick hardening rule, but the second Armstrong-Frederick hardening rule has also an effect on the ratcheting simulation. Highlights: Experiments show that 304SS exhibits Masing behavior when the cycling strain range is lower than ±0.9%. Ratcheting strain in 304SS obviously presents rate-dependent effect. Optimum parameters of the CHK-3-ISO-1 model are obtained just using the stress-based objective function. The proposed pseudo-percent allocation method is helpful in optimizing the parameters of CHK-3-ISO-1 model.